(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: In 2023, 45% of the Dutch population met the Dutch Physical Activity (PA) guidelines. The Dutch government aims to increase this to 75% in 2040. The guidelines consist of two components: PA-minutes of at least moderate intensity spread throughout the week, and bone/muscle-strengthening activities. In order to effectively address individuals who do not meet the guidelines, this group first needs to be identified further. The aim of the current study is to define and describe ‘inactive’ and ‘insufficiently active’ groups. This information can help policymakers in designing targeted PA strategies. Methods: Data of the Dutch Health Survey/Lifestyle Monitor (Statistics Netherlands (CBS)/RIVM) from 2023 was used (n = 9,033). Individuals who do not reach ≥30 minutes of at least light intensity PA (metabolic equivalent (MET) ≥1.6) per week (adults, age ≥18) or per day (children, age 4–17) are considered ‘inactive’. The group that does not match the ‘inactive’ criteria, nor complies to the PA guidelines, is labelled ‘insufficiently active’. Demographic and health characteristics of both groups were studied. The ‘insufficiently active’ group was examined further by looking at duration, frequency, and nature of reported PA. Specifically the spreading of PA throughout the week was studied, maintaining a conservative threshold of seven moments per week. Results: In 2023, 1.6% of the Dutch population (age ≥4) was inactive and 53.3% classified as insufficiently active. Both groups showed overrepresentation of people with disabilities/chronic illnesses or poor perceived health. The ‘insufficiently active’ individuals showed a lot of variation in PA behaviour. Some already reach sufficient PA minutes, but at too low an intensity and/or insufficiently spread these throughout the week. By engaging in PA a little more often (1–2 additional moments per week), the proportion of the Dutch adult population meeting the guidelines could increase from 44.0% to 56.0%. Conclusion: The current results show characteristics of the inactive and insufficiently active groups, and provide new building blocks for PA policy. By adding a few weekly PA moments, the percentage of Dutch adults meeting the guidelines could increase drastically. Support/Funding Source: This research was funded by the Ministry of Health, Welfare and Sport of The Netherlands.